Integrating Individual Differences into TESOL Strategies for Overcoming Communication Barriers - Cui, Zhihan (Journal of Theory and Practice in Education and Innovation, 2025)
This study examines how TESOL strategies grounded in individual difference theory can systematically address communication barriers in foreign language classrooms. Moving beyond traditional standardized approaches that overlook critical variations in learners’ language aptitude, cognitive styles, and affective profiles, the research deconstructs the multifaceted origins of linguistic, psychological, and sociocultural communication obstacles. A three-tiered framework is proposed, combining layered diagnostic protocols with adaptive intervention methods. The implementation involves developing multidimensional assessment tools and classroom observation matrices to inform differentiated task design, flexible grouping systems, and metacognitive scaffolding techniques—all tailored to individual learning profiles. Central to this approach is cultivating intercultural mediation competence through contextualized practice. Empirical evidence demonstrates that such differentiation strategies significantly enhance oral fluency, reduce communication apprehension, and foster cultural adaptability across diverse learner cohorts.